(untitled) (Revista Apotheke, 2018)
This work seeks to show that John Dewey offers valuable contribution to think on educational problems of today. To fulfill this goal, the work studies Dewey’s Art as experience in order to discuss the link established by the author between the two concepts that form the title of the book – art and experience. The results of the study are transported to education – subject not focused in that book – considering the educational scenery of today. The methodology is the rhetorical analysis, in accordance with the works of the Research Group Rhetoric and Argumentation in Pedagogy (USP/CNPq), whose bases are in Aristotle, especially in Topics and Rhetoric, according to the interpretation made by Chaïm Perelman and other researchers linked to the contemporary movement that promotes the revision of Aristotelian philosophy. The conclusions of the work emphasize that the transposition of Dewey’s aesthetic to education brings several contributions to educators, supporting innovative measures, such as the use of the arts in teaching and the creation of new methods for teaching art, and also offering inspiration to transform education in a rewarding and humanizing experience. Such contributions should be however confronted with political radicalism that is present in the exam made by Dewey about contemporary culture.